2017
DOI: 10.4171/jncg/11-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Factorization homology and calculus $\textit{à la}$ Kontsevich Soibelman

Abstract: We use factorization homology over manifolds with boundaries in order to construct operations on Hochschild cohomology and Hochschild homology. These operations are parametrized by a colored operad involving disks on the surface of a cylinder defined by Kontsevich and Soibleman. The formalism of the proof extends without difficulties to a higher dimensional situation. More precisely, we can replace associative algebras by algebras over the little disks operad of any dimensions, Hochschild homology by factoriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…This is the derived tensor product of the right module of discs in M with the algebra A, over the little discs operad. As in Section 7 of [28], we can model this as (D θ…”
Section: Axiomatic Characterizationmentioning
confidence: 99%
“…This is the derived tensor product of the right module of discs in M with the algebra A, over the little discs operad. As in Section 7 of [28], we can model this as (D θ…”
Section: Axiomatic Characterizationmentioning
confidence: 99%
“…We abuse terminology by referring to it as Kontsevich-Soibelman operad. In a nutshell, KS ⊂ DCyl is the maximal simplicial subcomplex spanned by vertices correponding to those tuples which do not contain the color C. It is not difficult to check that KS is equivalent to that of [16] or [23,Section 11.2]. In [11], a version of KS is called the cylinder operad.…”
Section: Mult Tmentioning
confidence: 99%
“…It contains two colors, D and C M , such that the full suboperad spanned by the color D is the E 2 -operad. In [11], it was shown that a combinatorial dg operad KS comb , which is a certain dg version of KS, acts on the pair of the Hochschild cochain complex and the Hochschild chain complex of an associative algebra (A ∞ -sense), and in [16] an algebraic structure on the Hochschild pair over KS was constructed for a ring spectrum by means of the Swiss-cheese operad conjecture [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Equivalently one can work in a suitable model category of E θ n -algebras, see [33], [26], [21], or [34]. A definition of E θ n -cell structures in terms of push outs is used to define cofibrant replacement for algebras over operads, e.g.…”
Section: Cell Attachmentsmentioning
confidence: 99%